2011
DOI: 10.4103/0256-4947.83217
|View full text |Cite
|
Sign up to set email alerts
|

Role of cell adhesion molecules in acute ischemic stroke

Abstract: BACKGROUND AND OBJECTIVES:The expression of soluble adhesion molecules inter-cellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1), besides activation of endothelial cells and transendothelial migration of leukocytes, play an important role in inflammation and progression of ischemic injury after acute stroke. The aim of this study was to determine serum levels of soluble ICAM-1 and VCAM-1 in patients with acute ischemic stroke and controls and correlate them according to etiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 23 publications
1
61
0
Order By: Relevance
“…ICAM-1, which is upregulated after ischemic and hemorrhagic injury, plays an important role in inducing neuro-inflammation and mediating the progression of injury after acute stroke. 5,45 Our results are in line with the work of Thimmulappa et al and Zhao et al who found that activators of the Nrf2/ARE pathway reduced myeloperoxidase, an inflammatory mediator in experimentally induced sepsis, and ICH. 46,47 …”
Section: Discussionsupporting
confidence: 91%
“…ICAM-1, which is upregulated after ischemic and hemorrhagic injury, plays an important role in inducing neuro-inflammation and mediating the progression of injury after acute stroke. 5,45 Our results are in line with the work of Thimmulappa et al and Zhao et al who found that activators of the Nrf2/ARE pathway reduced myeloperoxidase, an inflammatory mediator in experimentally induced sepsis, and ICH. 46,47 …”
Section: Discussionsupporting
confidence: 91%
“…We included 5 studies [21,27,28,50,51] (344 lacunar strokes) but available data did not permit meta-analysis. In 1 study [21] significantly higher ICAM was found in lacunar stroke versus non-stroke controls acutely; another study [50] found ICAM significantly higher in lacunar versus non-stroke controls chronically.…”
Section: Plasma Markersmentioning
confidence: 99%
“…Here, 3 studies were included [27,28,51] (121 lacunar strokes) but available data did not permit meta-analysis. Results suggested no difference between lacunar stroke and non-stroke acutely and no difference between lacunar and non-lacunar stroke acutely.…”
Section: Plasma Markersmentioning
confidence: 99%
“…; Supanc et al . ). Injured neurons, activated glial cells, and recruited leukocytes secrete cytokine and MMPs that further exacerbate tissue injury (Yang et al .…”
Section: Discussionmentioning
confidence: 97%
“…Post-ischemic inflammation can aggravate both BBB degradation and neuronal apoptosis (Terao et al 2008;Lakhan et al 2009). Post-ischemic inflammation is initiated through the synthesis of adhesion molecules and chemokines in injured brain cells and is exacerbated by the recruitment of circulating inflammatory cells (Jin et al 2010;Supanc et al 2011). Injured neurons, activated glial cells, and recruited leukocytes secrete cytokine and MMPs that further exacerbate tissue injury Feng et al 2011;del Zoppo et al 2012).…”
Section: Discussionmentioning
confidence: 99%